Marketing—A Critical Policy for Today's Information Centre - Ganguly, S.; Kar, Debal C. (DESIDOC Journal of Library & Information Technology, 2003)
The challenge of coping with the changes in social, technological, economicalenvironment has forced the library and information centres (LICs) to change their time honoured old practices. Pressure for accountability and the emergence of enterprise culture has led the library and information professionals to take aggressive actions for financial self-sufficiency. Hence in the present era, the library and information managers (LIMs) will have to think of producing an information product and project it in the market for potential users which will help to generate revenue. TERI-LIC contributes in different products and services which are generated in-house. These wide range of products and services are marketed and disseminated to the end users through an effective marketing strategy and also in coordination with separate marketing service area. Most of these products and services are price- based for the self-sustenance of the Centre. http://dx.doi.org/10.14429/dbit.22.3.3565